Combatting Hunger, Malnutrition and Food Insecurity - A Scourge of Global Drylands: A Narrative Review - Feng, Haiying; Squires, Victor R. (Discoveries in Agriculture and Food Sciences, 2025)
This article is a Narrative Review that sieves through available information, summarizes trends and reports on published efforts to minimize the impact of factors contributing to food insecurity in the world’s drylands. Statistical data, comments by specialists (both foreign and domestic) and the results of our own observations are synthesized here. There are three main themes: 1. The policy and practice around the protection of agricultural land and national food security through a series of case studies from Africa. 2. Diverse responses to heightened food safety anxiety associated with climate change and an increasingly disembedded food system and disrupted supply chains. 3. The marginalization of small-scale, including subsistence farmers (and their knowledge) through the vertical integration and modernization of agricultural production. Food security is a major issue in the world’s drylands that occupy over 42% of the land surface. Multiple global stressors of climate change, drought, famine and war make it increasingly difficult to meet the dietary needs of large sections of the population. Here we discuss the nature of food security (and insecurity), its global drivers, and opportunities to enhance food security, with an emphasis on drylands. Examples are drawn largely from the African continent. We show that food security is complex, multi-faceted and largely intractable. Improved food security will require greater integration among sectors involved in food supply, access and availability, sustained involvement by governments and financial institutions to support existing food programs, and a greater emphasis on climate smart agriculture and indigenous knowledge, particularly at the local scale. A multidisciplinary approach is critical, with specialists in food science, agriculture, engineering, logistics and economics all playing a role in tackling this long-standing challenge.